Factor VIII/IX inhibitor testing practices in the United Kingdom: Results of a UKHCDO and UKNEQAS national survey. Issue 3 (2nd March 2021) - Batty, Paul; Riddell, Anne; Kitchen, Steve; Sardo Infirri, Sofia; Walker, Isobel; Woods, Tim; Jennings, Ian; Hart, Daniel P.
Abstract: Introduction: Inhibitor formation is the greatest challenge facing persons with haemophilia treated with factor concentrates. The gold standard testing methodologies are the Nijmegen‐Bethesda assay (NBA) for FVIII and Bethesda assay (BA) for FIX inhibitors, which are affected by pre‐analytical and inter‐laboratory variability. Aims: To evaluate inhibitor testing methodology and assess correlation between self‐reported and actual methodology. Methods: Methodology was evaluated using a survey distributed alongside a UK National External Quality Assessment Service Blood Coagulation external quality assurance (EQA) exercise for FVIII and FIX inhibitor testing. Results: Seventy four survey and EQA exercise responses were received (response rate 63.2%), with 50 paired survey/EQA results. 47.1% (33/70) reported using the NBA and 42.9% (30/70) the BA for FVIII inhibitor testing. Review of FVIII inhibitor assay methodology demonstrated discrepancy (self‐reported to actual) in 64.3% (BA reporting) and 27.6% (NBA reporting). Pre‐analytical heat treatment was used by 32.4%, most commonly 56°C for 30 minutes. Assay cut‐offs of 0.1‐1.0 BU/mL were reported. EQA samples (acquired FVIII and congenital FIX) demonstrated titres and coefficients of variation (CV) of 3.1 BU/mL (0.7‐15.4 BU/mL; CV = 43%) and 18.0 BU/mL (0‐117 BU/mL; CV = 33%), respectively. No significant assay or laboratory factors were found to explain this variance, which could have resulted in change in management for 6 patients (5 misclassified high‐titre FVIII inhibitors and 1 false negative for a FIX inhibitor). Conclusions: Heterogeneity was seen at each stage of assay methodology. No assay‐related factors were found to explain variation in inhibitor titres. Further standardization is required to improve inhibitor quantification to guide patient care.